A Republican Europe of States: synopsis and introduction to the symposium. Issue 4 (7th June 2022) - Bellamy, Richard
ABSTRACT: This introduction offers a synopsis of the book, A Republican Europe of States, outlining its main arguments, followed by an overview of the symposium.